2009
DOI: 10.1128/jcm.02142-08
|View full text |Cite
|
Sign up to set email alerts
|

Major Mycobacterium tuberculosis Lineages Associate with Patient Country of Origin

Abstract: Over recent years, there has been an increasing acknowledgment of the diversity that exists among Mycobacterium tuberculosis clinical isolates. To facilitate comparative studies aimed at deciphering the relevance of this diversity to human disease, an unambiguous and easily interpretable method of strain classification is required. Presently, the most effective means of assigning isolates into a series of unambiguous lineages is the method of Gagneux et al. (S. Gagneux et al., Proc. Natl. Acad. Sci. USA 103:28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(151 citation statements)
references
References 35 publications
12
136
2
1
Order By: Relevance
“…Of these 5 subgroups, groups 2 to 5 represent the Beijing sublineage (27,47,48). Interestingly, the C507G SNP is restricted to the phylogenetically related East African/Indian (lineage 3) and East Asian lineages, while the C601T SNP is unique to the Beijing sublineage of the East Asian lineage ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 5 subgroups, groups 2 to 5 represent the Beijing sublineage (27,47,48). Interestingly, the C507G SNP is restricted to the phylogenetically related East African/Indian (lineage 3) and East Asian lineages, while the C601T SNP is unique to the Beijing sublineage of the East Asian lineage ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…tuberculosis H37Rv was originally obtained from the American Type Culture Collection (ATCC 27294). The majority of clinical M. tuberculosis isolates used in this study were originally reported as part of an earlier molecular epidemiology investigation (48) in which isolates were classified according to the presence of large-sequence polymorphisms (LSPs) (47). Isolate 98_1663 was kindly provided by S. Gagneux (Swiss Tropical and Public Health Institute, Basel, Switzerland) and P. Small (Stony Brook University, Stony Brook, NY).…”
Section: Methodsmentioning
confidence: 99%
“…Today, we know that tuberculosis in humans is not caused by a single species, but instead by a complex of species including Mycobacterium tuberculosis, M. africanum, M. bovis, and M. canetti which originated from a common African ancestral strain 35,000-15,000 years ago [4]. To date, seven distinct phylogenetic lineages have been identified for the species M. tuberculosis and M. africanum, based on genomic polymorphisms [5,6], which differ with respect to global distribution, and in some causes infectivity and drug-resistance [7][8][9][10]. Compared to 1.2 million global deaths due to HIV/AIDS virus in 2014, TB has now emerged as the most common cause of human mortalities due to infectious disease with the toll reaching 1.5 million in same year [11].…”
Section: Early History Of Communicable Lung Diseasementioning
confidence: 99%
“…The classification of MTBC strains into these distinct lineages is relevant for evolutionary purposes but also for TB control. Indeed, these discrete lineages are associated with particular human populations or geographical regions and show differences in virulence and disease outcomes (12,20,21,35,41,53).…”
Section: Vol 48 2010mentioning
confidence: 99%